Методологія проектування систем відеоспостереження - Шкопотко, П. М.; Медведєв, Є. О. (ХНУРЕ, 2024)
The theory of video surveillance design, utilized components, selection of optimal equipment, and detailed virtual design are being discussed. Following the introduction to the concept of surveillance systems, there is a thorough discussion of design considerations.
Keywords: відеоспостереження; проектування систем відеоспостереження